Living donor kidney transplantation in crossmatch-positive patients enabled by peritransplant immunoadsorption and anti-CD20 therapy - Morath, Christian; Zeier, Martin; Süsal, Caner; Beimler, Jörg; Opelz, Gerhard; Scherer, Sabine; Schmidt, Jan; Macher-Göppinger, Stephan; Klein, Katrin; Sommerer, Claudia; Schwenger, Vedat (Transplant international, 2012)
Living donor kidney transplantation in crossmatch-positive patients is a challenge that requires specific measures. Ten patients with positive crossmatch results (n = 9) or negative crossmatch results but strong donor-specific antibodies (DSA; n = 1) were desensitized using immunoadsorption (IA) and anti-CD20 antibody induction. IA was continued after transplantation and accompanied by HLA antibody monitoring and protocol biopsies. After a median of 10 IA treatments, all patients were desensitized successfully and transplanted. Median levels of mean fluorescence intensity (MFI) of Luminex-DSA before desensitization were 6203 and decreased after desensitization and immediately before transplantation to 891. Patients received a median of seven post-transplant IA treatments. At last visit, after a median follow-up of 19 months, 9 of 10 patients had a functioning allograft and a median Luminex-DSA of 149 MFI; serum creatinine was 1.6 mg/dl, and protein to creatinine ratio 0.1. Reversible acute antibody-mediated rejection was diagnosed in three patients. One allograft was lost after the second post-transplant year in a patient with catastrophic antiphospholipid syndrome. We describe a treatment algorithm for desensitization of living donor kidney transplant recipients that allows the rapid elimination of DSA with a low rate of side effects and results in good graft outcome.